An empirical method for estimating surface area of aggregates in hot mix asphalt - R.P. Panda; Sudhanshu Sekhar Das; P.K. Sahoo (Journal of Traffic and Transportation Engineering (English ed. Online), 2016)
Bitumen requirement in hot mix asphalt (HMA) is directly dependent on the surface area of the aggregates in the mix, which in turn has effect on the asphalt film thickness and the flow characteristics. The surface area of aggregate blend in HMA is calculated using the specific surface area factors assigned to percentage passing through some specific standard sieve sizes and the imaging techniques. The first process is less capital intensive, but purely manual and labour intensive and prone to human errors. Imaging techniques though eliminating the human errors, still have limited use due to capital intensiveness and requirement of well-established laboratories with qualified technicians. Most of the developing countries like India are shortage of well-equipped laboratories and qualified technicians. To overcome these difficulties, the present mathematical model has been developed to estimate the surface area of aggregate blend of HMA from physical properties of aggregates evaluated using simple laboratory equipment. This model has been validated compared with the existing established methods of calculations and can be used as one of the tools in different developing and under developed countries for proper design of HMA.